Techno-economic analysis of a photovoltaic-fuel cell grid-connected hybrid energy system - Sheilla, Malious (Praise Worthy Prize, 2014)
This paper presents the techno-economic analysis of photovoltaic and fuel cell gridconnected system. The photovoltaic generator is an intermittent sources, thus the integration with fuel cell system is needed to provide continuous supply to the demand. The roles of fuel cell in this hybrid system are act as a backup power for the photovoltaic generation. This paper also described the modelling and simulation process of the proposed hybrid system. The modelling process of the system is divided into two parts which is using MATLAB/Simulink and HOMER software. Each characteristic of the system component is analyzed which include the photovoltaic, fuel cell and also the power conditioning converters. The simulation of various configurations in HOMER software focused on the net present cost, cost of energy, electricity produced and the reduction of CO2 emission. The proposed hybrid system can be an alternative solution to overcome the depletion of conventional fossil fuel and reduce the emission of carbon dioxide to be emitted to the atmosphere and preserve our environment.